Incorporation of timing properties into adaptive error control method for timely and reliable communication in industrial automation networks - Thanmayee Karimireddy (Systems Science & Control Engineering, 2017)
With the evolution of Industry 4.0, factory automation and manufacturing facilities are integrated and interconnected with each other, resulting in the formation of industrial automation networks. In industrial automation networks, transmission of high priority control packets help in monitoring and controlling the industrial machinery automatically. Proper working of these industrial automation networks require timely and reliable communication of control packets dealing with hard real-time traffic due to the presence of highly error prone wireless channels for communication. This study investigates the application of error control approaches to increase the reliability of control packet delivery within the strict deadline of industrial control applications of automation networks. In particular, Adaptive Sub MAC-Hybrid Automatic Repeat reQuest (ASM-HARQ) error control method is proposed in this paper to improve reliability of control packets delivery using both data redundancy and packet retransmission approaches. In order to ensure timely recoverability of any error packets at the receiver, an end-to-end delay packet retransmission metric, Tdelay, is developed in this study that helps in calculating the time required for packet retransmissions. The performance of ASM-HARQ method and its timing properties is shown through detailed analytical model and validated through simulated experiments in this study.